Comparative Transcriptome Analysis of Two Contrasting Chinese Cabbage (Brassica rapa L.) Genotypes Reveals That Ion Homeostasis Is a Crucial Biological Pathway Involved in the Rapid Adaptive Response to Salt Stress - Li, Na; Zhang, Zhihuan; Chen, Zijing; Cao, Bili; Xu, Kun (Frontiers in Plant Science, 2021)
Salt is the most important limiting factor in plant yield and quality. Different Chinese cabbage cultivars appeared different salt tolerances, but there are few studies attempting to elucidate the mechanism underlying this phenomenon. In this study, 100 mmol L-1 NaCl was found to be the most suitable treatment concentration according to a sprouting bag test of 39 Chinese cabbage cultivars, and through comprehensive comparison and analysis, the relative values of fresh weight and electrolyte leakage in leaves proved to be convenient indicators for the identification of salt tolerance in Chinese cabbage. We analyzed the physiological responses of Qinghua45 (salt-tolerant) and Biyuchunhua (salt-sensitive) in terms of the growth indexes, ion homeostasis and Photosynthesis, the results indicated that Qinghua45 could ensure osmotic regulation, ion homeostasis and photosynthesis under salt stress. Next, we compared the transcriptome dynamics of the two cultivars. Overall, 2,859 differentially expressed genes (DEGs) were identified, and the number of DEGs in Qinghua45 was significantly less than that in Biyuchunhua. VDAC promoted the release of Ca2+, which indirectly promoted the transport of Na+ to vacuoles through the SOS2 pathway. Cation/H (+) antiporter 17 and V-H+-ATPase improve the exchange of Na+ and H+ and maintain Na+ in the vacuoles, thereby reducing the injury affected by salt stress. Increases in galactinol synthase and soluble protein synthesis helped relieve osmotic stress caused by salt, together, they regulated the Na+ content and chlorophyll biosynthesis of the plant and enabled the plant to adapt to salt stress over time.